GAMBARAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG PENTINGNYA TES HIV DI UPT PUSKESMAS TEMBILAHAN KOTA TAHUN 2019 - Rina Analia; Haryati Astuti (STIKES HUSADA GEMILANG, 2020)
HIV infection in pregnant women effects to more than 90% infants during pregnancy, childbirth and breastfeeding. Without proper and early treatment, half of HIV-infected children will die before the second year and will increase HIV transmission by 3-5 times faster. The data on the pregnant women in Indragiri Hilir in 2018 were 15,841 people, and pregnant women who had HIV/AIDS examinations were 1,777 (13.3%). HIV examinations at the Health Center of Tembilahan Kota from January to June 2019 were 257 pregnant women who were tested and 112 were not. The purpose of the research was to find out the pregnant women knowledges and attitudes about the imortance of HIV test at the Health Center of Tembilahan Kota in 2019. This is a descriptive cross-sectional research. The populaion of the research were those all pregnant women who completed the HIV test in 2019, 398 people. The sample of the reserach (30 respondents) were taken through the use of Accidental Sampling technique. The results of the research clarifies that the frequency distribution of the majority of pregnant women had good knowledge of 16 people (53.3%) and the majority of positive attitudes were 18 people (60%). It is highly expected that this will provide much contribution to the Health Center of Tembilahan Kota in maintaing and improving HIV counseling services at HIV/AIDS counters.